Oikonymic Transformations in Romania in the Second Half of the Twentieth Century. (3rd April 2017) - Felecan, Oliviu
Abstract : The end of World War II caused numerous changes in the urban toponymy of Central and Eastern Europe. For instance, Brașov, one of the most important Romanian cities, bore the name Orașul Stalin ("Stalin city") for 10 years. It was an homage paid to the Soviet leader, whose name could be identified in another 13 oikonyms in the Eastern bloc, behind the Iron Curtain: Stalingrad — Volgograd (USSR), Stalin — Varna (Bulgaria), Stalinstadt — Eisenhüttenstadt (German Democratic Republic), Stalinograd — Katowice (Poland), Stalino — Donețk (Ukraine), and Sztálinváros — Dunaújváros (Hungary), among others. Some of the city names abusively altered during communism were readopted after the Revolution of 1989, which brought about the demise of the totalitarian regime in Romania. However, this was not the case with several hundred villages and communes whose names had been changed in 1964 because central authorities believed they displayed negative or inappropriate connotations.